Managing the drone revolution: A systematic literature review into the current use of airborne drones and future strategic directions for their effective control. (October 2020) - Merkert, Rico; Bushell, James
Abstract: Commercial and private deployment of airborne drones is revolutionising many ecosystems. To identify critical issues and research gaps, our systematic literature review findings suggest that historic issues such as privacy, acceptance and security are increasingly replaced by operational considerations including interaction with and impacts on other airspace users. Recent incidents show that unrestricted drone use can inflict problems on other airspace users like airports and emergency services. Our review of current regulatory approaches shows a need for further policy and management response to both manage rapid and efficient drone usage growth, and facilitate innovation (e.g. intraurban package delivery), with one promising strategic response being low altitude airspace management (LAAM) systems for all drone use cases. Highlights: Historic issues such as privacy, acceptance and security increasingly replaced by operational and strategy considerations. The literature on drones is wide and not significantly concentrated in any particular source or to any author/ institution. Drone usage can be categorised into 4 uses: monitoring/inspection/data collection, photography, recreation and logistics. Low altitude airspace management (LAAM) as strategic response for all drone use cases.